The Influence Apparatus Competence and Use Financial System Applications on Financial Management Transparency - Irawan, Bambang; Herlambang, Toni; Sanosra, Abadi; Nursaid, Nursaid; Qomariah, Nurul (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2024)
Transparency is openness regarding the Village APBD which allows the community to know and gain access to the widest possible information about village finances. This research aims to determine the significant positive influence of the competence of village officials, the use of the SISKEUDES application on the transparency of village financial management in Probolinggo Regency. The population of this research is the Village Government in Probolinggo Regency, taking 100 respondents as samples. The data collection method in this research used a questionnaire distributed to all respondents. Data analysis in this study used SEM-PLS with WarpPLS. The research results show: 1) the higher the competence of village officials, the more significant positive influence it has on the transparency of village financial management as indicated by the results of β = 0.29 and p-value = 0.002; 2). The higher the use of the Siskeudes application, the more significant positive influence it has on the transparency of village financial management as indicated by the resulting β value = 0.38 and p-value < 0.001.